Determinantes de spread de fundos de investimento em direitos creditórios - Zacchello, Daniel (2010)
The main purpose of this study is to identify the determinants of a Receivables Fund (FIDCs) spread. As the previously published papers were about debentures, this one is pioneer in terms of FIDCs. Indeed, understanding the determinants of a FIDCs’ issuance is mandatory for companies which access capital markets to obtain funds. Between 2002 and 2009, the study analyzed 113 public issuances indexed to CDI that had a pre-defined maturity and at least two investors. Those issuances were subject to four Ordinary Least Squares (OLS) regressions. The first regression focused on the variables that affected the rating. The second one excluded all rating related variables and had spread as the dependent variable, while all the others were independent variables. The third one tested a potential non-linearity relation between spread and rating, while the fourth regression tested the spread against all other variables, including those ones related to the rating. The results pointed out that rating is indeed a good determinant for the spread, as well as the issuance volume, the financial institution responsible for the FIDCs’ custody and the macroeconomic environment. These three variables also contributes to determine the rating, along with the number of investors and issuers and if the underlying assets were eventually delivered. The study also concluded that there is no evidence of linearity between spread and rating in FIDCs. The major contribution of this study is to present on first hand a thorough analysis on variables that affect a new type of fixed income investment, the FIDCs, such as the asset nature, credit risk diversification levels and quantity of issuers. The main purpose of this study is to identify the determinants of a Receivables Fund (FIDCs) spread. As the previously published papers were about debentures, this one is pioneer in terms of FIDCs. Indeed, understanding the determinants of a FIDCs’ issuance is mandatory for companies which access capital markets to obtain funds. Between 2002 and 2009, the study analyzed 113 public issuances indexed to CDI that had a pre-defined maturity and at least two investors. Those issuances were subject to four Ordinary Least Squares (OLS) regressions. The first regression focused on the variables that affected the rating. The second one excluded all rating related variables and had spread as the dependent variable, while all the others were independent variables. The third one tested a potential non-linearity relation between spread and rating, while the fourth regression tested the spread against all other variables, including those ones related to the rating. The results pointed out that rating is indeed a good determinant for the spread, as well as the issuance volume, the financial institution responsible for the FIDCs’ custody and the macroeconomic environment. These three variables also contributes to determine the rating, along with the number of investors and issuers and if the underlying assets were eventually delivered. The study also concluded that there is no evidence of linearity between spread and rating in FIDCs. The major contribution of this study is to present on first hand a thorough analysis on variables that affect a new type of fixed income investment, the FIDCs, such as the asset nature, credit risk diversification levels and quantity of issuers.